KINERJA, KESEJAHTERAAN ANGGOTA, DAN STRATEGI PENGEMBANGAN KOPERASI UNIT DESA - Vani Sintiya Dewi; Dyah Aring Hepiana Lestari; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
The purposes of this research are to find out and compare performance and member prosperity rate of the Rural Cooperatives (KUD) Mitra Subur (MS) and KUD Tri Tunggal Sido Waras (TTSW), and determine the development startegy of developing the KUD TTSW in Central Lampung.  This research uses a case study method in KUD MS, Gunung Sugih district and KUD TTSW, Bumi Ratu Nuban district, Central Lampung.  The locations were choosen  purposively with consideration that both  cooperatives have the same type, saving and loans business units, members’ main jobs are rice farmers, and have total members of almost same number.  Data were collected in February – March 2016.  The results showed that: KUD MS had a good quality while KUD TTSW has a medium quality.  According to Statistic Bureau indicator (2012) members’ of KUD MS and KUD TTSW belong to not prosperous category, therefore both KUDs need to improve the members prosperity so the cost of food will be on GKM.   Overall, prosperity rate of KUD MS’s members is better than that of KUD TTSW.  The priority strategy that can be used in development of KUD TTSW is the application of modern technology such as an internet access to increase the cooperative’s income.                                                                                                       Key words : active, cooperative, performance, prosperity, strategy